Odpowiedzi

2009-11-09T15:52:38+01:00
C) 2t+1-6tkwadrat-3t=6tkwadrat-t+1
d) 9ab-21-31(ab)kwadrat+47ab=-31(ab)kwadrat+56ab-21
e) -5xkwadrat-6xy+5xy+6ykwadrat=-5xkwadrat-xy+6ykwadrat
2009-11-09T16:24:46+01:00
C)(2t+1)*(1-3t)=2t-6t²+1+3t=5t-6t²+1
d) (3ab-7)*(3-7ab)=9ab-21a²b²-21-49ab=-21a²b²-40ab-21
e) (-x+y)*(5x+6y)=-5x²-6xy+5xy+6y²=-5x²+6y²-xy
h) (ab-a)*(2ab+6a)=2a²b²+6a²b-2a²b-6a²=2a²b²+4a²b-6a²
2009-11-09T18:05:02+01:00
C)
( 2t + 1)(1 - 3t)
2t-6t²+1-3t
-t-6t²+1

d)
( 3ab - 7)(3 - 7ab)
9ab-24ab²-21+49ab
58ab-24ab²-21

e)
( -x + y) ( 5x + 6y)
-5x²-6yx+5xy+6y²
-5x²-xy+6y²

h)
( ab-a) (2ab + 6a)
2a²b²+6a²b-2a²b-6a²
2a²b²+4a²b-6a²